Fecundity (Rhizophora mucronata Lamk.) towards Low-Standing Puddles at Marobo River Central Mawasangka Buton, Southeast Sulawesi - Sutriani Kaliu (Journal of Biological Science and Education, 2020)
Rhizophora mucronata Lamk. is widely used for rehabilitation of mangrove areas because the fruit is easily obtained, sowing and can grow in areas of high or low tidal inundation. This study aims to know the effect of high-low waterlogging on fecundity (the development of fruit into mature propagules) Rhizophora mucronata Lamk and to determine the characteristics of the ecosystem environment on the Rhizophora mucronata Lamk fecundity. The study was conducted in the Marobo River Mawasangka, Buton Tengah, Southeast Sulawesi. Observations were made in the downstream area towards the headwaters of the river. Each zone is made 100m baseline; the distance between sub-transects is 25m. Each subplot was plotted by making 2x2m2 quadrant plots for Rhizophora mucronata Lamk. earning productive interest, propagules and seedlings, making it easier to count the number of seedlings. Fecundity (counting the number of fruits until the propagules ripen each tree) and measurement of environmental chemical physics. Fecundity comparison analysis between the two zones by using a t-test. The results of the study based on the t-test, there is a significant difference in the percentage of fruit and propagules in zones 1 and 2 with a value of p 0.05, the highest average fruit is in zone 1 (79.9%). The highest propagule average is in zone 2 (33, 9%), highly influential in the high-low of puddles with salinity levels of zone 1 (20%) and zone 2 (10%). The results showed that there was a high-low waterlogging effect on the Rhizopora mucronata Lamk fecundity